Rural community-based nurses' self-reported knowledge and skills in the provision of psychosocial care to palliative and end-of-life clients and carers. Issue 6 (December 2022) - Ristevski, Eli; Leach, Michael; Bolton, Ellen; Spargo, Melissa; Byrne, Anny; Khalil, Hanan
Abstract: Objective: This study examined rural community-based nurses' self-reported knowledge and skills in the provision of psychosocial care to rural residing palliative and end-of-life clients and carers. We further sought to determine correlates of knowledge gaps to inform workforce education and planning. Method: Nurses from a rural area of Victoria, Australia, were invited to complete an electronic questionnaire rating their knowledge against 6 national palliative care standards and 10 screening and assessment tools. A 5-point scale of (1) No experience to (5) Can teach others was used to rate knowledge. Results were classified into three categories: practice gaps, areas of consolidation, and strengths. Descriptive and logistical regression was used to analyze data. Results: A total of 122 of 165 nurses (response rate = 74%) completed the survey. Of these nurses, 87% were Registered Nurses, 43% had ≥10 years' experience in palliative care, and 40% had palliative care training. The majority of practices across the standards and screening and assessment tools were rated as knowledge strengths ( N = 55/67, 82%). Gaps and areas of consolidation were in the use of client and carer assessment tools, the care of specific populations such as children, supporting carers with appropriate referrals, resources, and grief, and facilitating the processes of reporting a death to the coroner. Lack of formal training and lower years of experience were found to be associated with practice gaps. Significance of results: Our study found rural nurses were confident in their knowledge and skills in the majority of psychosocial care. As generalist nurses make up the majority of the rural nursing workforce, further research should be undertaken on what educational strategies are needed to support and upskill rural community-based nurses to undertake formal training in palliative care.